Az Erdélyi Fejedelemség önállóságának földrajzi alapjai - Nagy, Miklós Mihály (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The end of the Turkish Empire’s territorial expansion in Southern Europe was one of the determining phenomenons of territorial development in the continent in the 16th— 17th century. This geographical process had an attendant phenomenon as buffer states emerged in the borders of the Empire from which Transylvania was the key element. The sovereign Transylvania located out of the main theatre of the Habsburg-Turkish conflict constituted a closed politico-geographical and geopolitical unit in the Carpathian basin. The sovereignty and the important historical role of the Principality were determined by geographical factors. The study is about these factors and geographical powers of the Transylvanian basin with close connections to other military-geographical factors of Habsburg-Turkish conflict.